Tailored Quinolines Demonstrate Flexibility to Exert Antitumor Effects through Varied Mechanisms-A Medicinal Perspective - Sharma, Sachin; Singh, Arshdeep; Sharma, Sahil; Sharma, Ram; Singh, Jagjeet; Kinarivala, Nihar; Nepali, Kunal; Liou, Jing P. (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Quinoline is considered to be a privileged heterocyclic ring owing to its presence in diverse scaffolds endowed with promising activity profiles. In particular, quinoline containing compounds have exhibited substantial antiproliferative effects through the diverse mechanism of actions, which indicates that the heteroaryl unit is flexible as well as accessible to subtle structural changes that enable its inclusion in chemically distinct anti-tumor constructs. Methods: Herein, we describe a medicinal chemistry perspective on quinolines as anticancer agents by digging into the peer-reviewed literature as well as patents published in the past few years. Results: This review will serve as a guiding tool for medicinal chemists and chemical biologists to gain insights about the benefits of quinoline ring installation to tune the chemical architectures for inducing potent anticancer effects. Conclusion: Quinoline ring containing anticancer agents presents enough optimism and promise in the field of drug discovery to motivate the researchers towards the continued explorations on such scaffolds. It is highly likely that adequate efforts in this direction might yield some potential cancer therapeutics in the future.
Keywords: heterocycle